2023
DOI: 10.3390/metabo13040472
|View full text |Cite
|
Sign up to set email alerts
|

Metabolomic-Based Studies of the Intake of Virgin Olive Oil: A Comprehensive Review

Abstract: Virgin olive oil (VOO) is a high-value product from the Mediterranean diet. Some health and nutritional benefits have been associated with its consumption, not only because of its monounsaturated-rich triacylglycerols but also due to its minor bioactive components. The search for specific metabolites related to VOO consumption may provide valuable information to identify the specific bioactive components and to understand possible molecular and metabolic mechanisms implicated in those health effects. In this r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 64 publications
(93 reference statements)
0
3
0
Order By: Relevance
“…Several factors may influence the biochemical impact of OO including components quantitative and qualitative profiles, absorption, and metabolism. In their comprehensive review, Vazquez-Aguilar et al [ 13 ] used metabolomics to unravel available evidence from human, animal, and in vitro studies on the metabolic effects of VOO or its bioactive compounds. Despite heterogeneity between studies, the impact of regular VOO consumption on carbohydrate, lipid, and amino acid metabolism was shown, although specific metabolites could not be identified.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Several factors may influence the biochemical impact of OO including components quantitative and qualitative profiles, absorption, and metabolism. In their comprehensive review, Vazquez-Aguilar et al [ 13 ] used metabolomics to unravel available evidence from human, animal, and in vitro studies on the metabolic effects of VOO or its bioactive compounds. Despite heterogeneity between studies, the impact of regular VOO consumption on carbohydrate, lipid, and amino acid metabolism was shown, although specific metabolites could not be identified.…”
Section: Resultsmentioning
confidence: 99%
“…Regarding the nutritional profile, the major components of OO are fatty acids (98–99%) predominated by MUFA (55.3–86.5%; oleic acid and palmitoleic acid), followed by polyunsaturated fatty acids (PUFA) (3.5–21%; linoleic and linolenic acids), and saturated fatty acids (SFA) (8–25.1%; myristic, palmitic and stearic acids). On the other hand, minor components, which correspond to the unsaponifiable fraction, comprise between 1 to 2%, and include sterols, terpenoids and aliphatic alcohols, pigments, squalene, tocopherols (vitamin E), and polar phenolic compounds, as the most important ones [ 12 , 13 ]. Hydroxytyrosol and its derivatives stand out as the major phenolic compounds in VOO associated with positive health impacts.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Metabolomics offers a transdisciplinary approach for studying the metabolites present in olive oil. It involves analytical chemistry, chemometrics, and bioinformatics to comprehensively understand olive oil's metabolome [97]. The approaches and methodologies applied varied depending on the purpose of the study.…”
Section: Challenges and Future Directionsmentioning
confidence: 99%
“…Another clinical trial regarding the role of VOO in HDL functionality reported the impact of some metabolites (i.e., phenolic compounds) of VOO on the HDL triacylglycerol levels. Finally, a postprandial clinical trial involving the consumption of 40 mL of EVOO rich in oleocanthal demonstrated the anti-aggregation properties of the olive oil metabolite [97]. Postprandial studies are interesting investigations that explore the post-meal metabolomic response to olive oil consumption, revealing differences in the serum metabolite profiles compared with other edible oils.…”
Section: Challenges and Future Directionsmentioning
confidence: 99%